Development of shelf-life kinetic model for modified atmosphere packaging of fresh sliced mushrooms - Oliveira, Felisbela Maria Araújo (2012)
Mushrooms are highly perishable and their shelf-life depends on processing, package properties and environmental conditions during storage and distribution. The aims of this work were to evaluate the effect of temperature and number of film perforations on quality and develop shelf-life kinetic model for a modified atmosphere packaging (MAP) for sliced button mushrooms. Sliced mushrooms were packed in a tray, covered with cellophane film, and stored for 7 days at four levels of temperature (0,5, 10, and 15 C) and three levels of perforations at each temperature ranging the number of perforations from 1 (58 perforations per m2) to 6 (349 perforations per m2). Headspace gas composition and quality parameters (weight loss, pH, firmness and colour) were measured throughout the storage period. Increasing the storage temperature required an increase of the number of perforations in order to obtain the optimum MAP conditions. Temperature had a significant effect (p < 0.05) on quality of sliced mushrooms. Firmness was identified as a critical quality parameter; therefore, a kinetic model was developed to describe the influence of temperature on firmness and predict shelf-life of sliced mushrooms. Fresh sliced mushrooms had a shelf-life of 1, 2, 4, and 7.5 days at 15, 10, 5, and 0 C, respectively, under optimum MAP conditions.